Expressão de glicoesfingolipídeos no carcinoma espinocelular do trato aerodigestivo superior - Marques Filho, Marcílio Ferreira [UNIFESP] (2006)
Glycosphingolipids are integral constituents of cellular membrane, arranged in rafts, and with neoplasic cell anti-social behavior, like uncontrolled cell growth, invasiveness, and metastatic potential. AIM: However, there are few studies about glycosphingolipids (GSL) expression in squamous cell carcinoma (SCC). Since GSL are known to be tumor-associated markers we decided to perform a prospective study on the GSL profiles of SCC. METHOD: Specimens of 33 SCC and normal mucosa were obtained and GSLs were extracted and purified by reverse-phase chromatography on C18 column and alkaline hydrolysis in methanol. GSLs were quantified using densitometry of orcinol-stained HPTLC plates. RESULT: A significant increase of GSLs in SCC (3.57µg/mg) was observed as compared to normal mucosa (1.92µg/mg). In SCC, an increase of 2 to 3 times in the amounts of CDH, CTH, Globoside, and GM3 was observed in comparison to normal mucosa. The identification of GM3 as well as its increased expression in SCC was confirmed unequivocally by HPTLC immunostaining and indirect immunofluorescence using MAb DH2 (anti-GM3). BY analyzing SCC and normal mucosa CMHs by GC/MS, normal mucosa expresses only glucosylceramide whereas SCC cells express both glucosylceramide and galactosylceramide. CONCLUSION: The increase in the amount of GSLs in tumor tissue may represent changes of cell membrane microdomains resulting from the malignant transformation process, which is responsible for greater cell-cell or cell-matrix interaction thereby increasing their potential for infiltration and metastasis.